Extraskeletal osteosarcoma: MDM2 and H3K27me3 analysis of 19 cases suggest disease heterogeneity. Issue 1 (19th April 2018) - Makise, Naohiro; Sekimizu, Masaya; Kubo, Takashi; Wakai, Susumu; Watanabe, Shun‐ichi; Kato, Tomoyasu; Kinoshita, Takayuki; Hiraoka, Nobuyoshi; Fukayama, Masashi; Kawai, Akira; Ichikawa, Hitoshi; Yoshida, Akihiko
Abstract : Aims: Extraskeletal osteosarcoma (ESOS) is a sarcoma in the non‐skeletal tissue that directly produces neoplastic osteoid or bone. De‐differentiated liposarcoma (DDLPS) and malignant peripheral nerve sheath tumour (MPNST) are the two most common types of sarcoma that can harbour heterologous osteosarcomatous differentiation. We aimed to determine the potential relationship of ESOS to DDLPS and MPNST. Methods and results: We investigated MDM2 and H3K27me3 status in 19 cases of ESOS, two of which contained a low‐grade component. The ESOS affected deep soft tissues ( n = 10), superficial soft tissues ( n = 3) and organs ( n = 6). Among 10 deep soft‐tissue ESOS, six showed MDM2 amplification, four of which also harboured CDK4 co‐amplification. Both ESOS with a low‐grade component showed co‐amplification for MDM2 and CDK4 . Among the six organ‐based ESOS three giant cell‐rich ESOS showed an H3K27me3 deficiency (one in primary and two in metastatic sites). Using targeted next generation sequencing, an H3K27me3‐deficient ESOS showed EED homozygous deletion, while none of the three showed alterations in NF1, CDKN2A or SUZ12 genes. During median follow‐up of 20 months, all six patients with MDM2 ‐amplified ESOS lived for 3–103 months, while two of the three patients with H3K27me3‐deficient ESOS died from this disease in 4 and 20 months, respectively. Conclusion: We demonstrate that ESOS may include at least two small subsets: an MDM2 ‐amplified deep soft‐tissue ESOS (which may be related to DDLPS) and an H3K27me3‐deficient organ‐based ESOS (which is probably unrelated to MPNST). Larger studies are required to validate the present observations and investigate the clinical implications of such subcategorisation.